Source aspects in the reform of local self-government in Slovak Republic - Imrovič, Michal; Švikruha, Martin (Univerzita Pardubice, 2015)
To the basic principles of democratic state administration belongs administration of public affairs, what underlines importance of public administration in the modern state. Functions of the state are performed by the public administration in all spheres of society life. It has an important role in application of laws, including adoption of legislation, organizational activities, and ensuring public services. It also provides broad institutional tools of citizen participation in administrative processes at the local, regional or central level. In Slovakia is applied dual model of public administration, which consists of state and self-governing element. In our article, we focus on self-government part of the public administration, local self-government and its specifics, which resulted from management system applied on this level. It is concerning the element, which is very close to citizens, because it is a part of public administration that generally deals with issues of local or regional importance.
Keywords: public administration; local self-government; regional self-government; settlement structure; ctizen participation; decentralization; consolidation; municipality reform; H11; H76